First Cross-sectional Serological Survey on Besnoitia Besnoiti in Cattle in Italy - Rinaldi, Laura (2013)
A cross-sectional serological survey was conducted to evaluate the prevalence of besnoitiosis in cattle farms located in a region of southern Italy. A geographical information system (GIS) was used in order to uniformly sample the bovine farms (n = 88) throughout the entire region. Blood samples were collected from 528 autochthonous cattle and sera were tested for antibodies to Besnoitia besnoiti using an enzyme-linked immunosorbent assay test. The farm prevalence was 83.0 % (73/88), and the individual animal prevalence was 44.1 % (233/528). The availability of geo-referenced point or areal data on bovine besnoitiosis and the construction of prevalence maps by GIS are suggested for dissemination of information to veterinarians on this emerging infection in cattle.